A New Sensitive Serological Assay for Detection of Lentivirus Infections in Small Ruminants - Saman, Eric (American Society for Microbiology, 1999)
Lentivirus infections in small ruminants represent an economic problem affecting several European countries with important sheep-breeding industries. Programs for control and eradication of these infections are being initiated and require reliable screening assays. This communication describes the construction and evaluation of a new serological screening enzyme-linked immunosorbent assay (ELISA) for the detection of antibodies to maedi-visna virus (MVV) in sheep and to caprine arthritis encephalitis virus (CAEV) in goats. The solid phase is sensitized with a combination of the major core protein p25 of MVV produced in Escherichia coli and a peptide derived from the immunodominant region of the viral transmembrane protein gp46. The peptide carries an N-terminal biotin residue and is complexed with streptavidin prior to being coated. The new assay was evaluated with 2,336 sheep serum samples from different European countries with large differences in the levels of prevalence of MVV infections, and the results have been compared to those of the standard agar gel immunodiffusion test. Discrepant samples were analyzed by Western blotting with viral lysate, and most sera could be classified unambiguously. The estimated overall sensitivity of the new ELISA was 99.4% (95% confidence interval [CI], 98.4 to 99.8%) and the specificity was 99.3% (95% CI, 98.7 to 99.6%). A limited set of goat sera (n = 212) was also analyzed, with similar results. These data indicate that the new assay is a reliable tool that can be used in control and eradication programs for small ruminant lentivirus infections.